Performance assessment of the of Cyperus alternifolius and Chrysopogon zizanioide in greywater treatment with artificial wetland - Castillo Vargas, Juan (2024)
In Peru, the discharge of wastewater is due to the lack of treatment and sewage infrastructure in various areas of the country, mainly in new human settlements resulting from the unplanned and disproportionate growth of Peruvian cities. inside of city that constantly being impacted by the water that reaches its water mirrors, just due to the constant dumping of domestic wastewater mainly from the settlements located in the buffer zone. Therefore, we seek to improve the quality of the water of these canals using of horizontal flow subsurface wetlands using Chrysopogon zizanioide and Cyperus alternifolius species. We evaluated the removal of different parameters such as BOD5, turbidity and thermotolerant coliforms (TC). We found that the removal percentages for BDO5 were 66.87% for Cyperus alternifolius and 62.84% for Chrysopogon zizanioide. TC removal was 99.08% (Chrysopogon zizanioide) and 98.43% (Cyperus alternifolius) and to turbidity, both species reached high removals, up to 99.18%.